The investigation of antimicrobial and antifungal activity of some Artemisia L. species - Roman Andriiovych Hrytsyk; Roman Volodymyrovych Kutsyk; Oxana Ivanivna Yurchyshyn; Оxana Аnatolievna Struk; Igor Vladimirovich Kireev; Andrii Romanovych Grytsyk (Pensoft Publishers, 2021)
Background: Throughout history pathogenic microorganisms cause infectious diseases. Medicinal herbs play an important role in human life because they are used for the therapy and production of herbal remedies. Therefore, it is relevant to study the antibacterial activity of medicinal herbs including Artemisia L. species. Aim: The purpose of this study was to investigate the antimicrobial and antifungal activity of Artemisia L. species extracts and to identify their synergistic antimicrobial effects with erythromycin against skin isolates of Staphylococcus aureus with different mechanisms of MLS-resistance. Materials and methods: Artemisia absinthium L. herb extracts (AAs-4, AAs-7, AAs-9), Artemisia vulgaris L. herb extracts (AV-4, AV-7, AV-9) and Artemisia abrotanum L. herb extracts (AAr-4, AAr-7, AAr-9) were used in this study (solvents - 40%, 70% and 90% ethyl alcohol respectively). The determination of antimicrobial activity of extracts was performed using clinical isolates of antibiotic susceptible and antibiotic resistant microorganisms. Bacterial cultures were identified on the basis of the biochemical microtests "STAPHYtest 16", "ENTEROtest 24", "NEFERMENTtest 24" taking into account the complex of their morphological and cultural properties in accordance with the recommendations of the 9th edition of "Bergey's Manual of Systematic Bacteriology". Yeast-like fungi cultures were identified on the basis of 40 biochemical tests with the help of the VITEK 2 system using the VITEK 2 YST ID card. The synergism of the antimicrobial activity of extracts with erythromycin was investigated using the clinical isolate of Staphylococcus aureus with the non-inductive MLS-resistance mechanism (resistant to erythromycin at minimum bacteriostatic concentration of 125 μg/ml and minimum bactericidal concentration of 250 μg/ml without induction of resistance to clindamycin). Research results: The evaluation of Artemisia L. herb extracts activity was carried out using standard strains of microorganisms which are recommended by the WHO. The results of the conducted studies indicate that Artemisia L. herb extracts are able to reduce the growth of microorganisms. The investigated extracts showed the potent bacteriostatic action against the cocci or rod-shaped microflora. The antimicrobial activity of Artemisia L. herb extracts directly depends on the concentration of ethanol as the solvent. Artemisia vulgaris L. herb extracts (solvents - 70% and 90% ethanol) and Artemisia abrotanum L. herb extract (solvent - 90% ethanol) show synergism of antimicrobial activity with erythromycin in relation to Staphylococcus aureus with efflux mechanism of MLS-resistance. The obtained Artemisia L. herb extracts can be used to create antifungal drugs, as well as antimicrobial drugs (against gram-positive and gram-negative bacteria).